Effects of bamboo powder and rice husk powder conditioners on sludge dewatering and filtrate quality. (October 2017) - Wang, S.; Yang, Y.K.; Chen, X.G.; Lv, J.Z.; Li, J.
Abstract: Decreasing sludge moisture content and increasing sludge organic content are the main difficulties encountered in sludge incineration. The use of inorganic lime as a sludge conditioner decreases sludge organic content and increases the concentration of contaminants, which present severe environmental hazards, in the dewatered filtrate. Thus, in the present study, two agricultural wastes, bamboo powder (BP) and rice husk powder (RHP), were selected to replace lime as sludge conditioners along with cationic polyacrylamide and FeCl3 . Experimental results showed that BP and RHP acted as skeleton builders that decreased sludge compressibility from 1.08 to 0.76 and 0.78and increased the ultimate heating values of sludge cake. In addition, the addition of BP and RHP decreased the chemical oxygen demand, total nitrogen, and total phosphorus of the filtrate. Coordinated conditioning with BP and RHP decreased capillary suction time, specific resistance to filtration, and moisture content decreased. Therefore, the replacement of quick lime with BP and RHP could help achieve the stable operation of sludge incineration and wastewater treatment plants. Highlights: Agricultural wastes were selected to substitute lime to condition sludge. The compressibility coefficient significantly decreased when BP and RHP applied. BP and RHP could serve to enhance separate sludge incineration. Contaminants contents within filtrate obviously decreased by BP and RHP conditioning. Hypothesis of sludge dewatering process by different conditioners was depicted.